Pengaruh risiko kredit terhadap permodalan dengan efisiensi sebagai variabel intervening - Achmad Achmad; Emanuel Kristijadi (Journal of Business & Banking, 2020)
Capital for the banking industry as a safeguard against possible risks is very important. This study aims to analyze whether NPL, CKPN, LAR, and BOPO have a significant effect on CAR. This research uses secondary data, taken by documentation method. The data were obtained from the Bank’s financial reports (Book 3) for the 2016-2019 period from the published reports of the Financial Services Authority (OJK). The data were analyzed using a descriptive analysis and Multiple Regression Analysis (MRA). The results show that NPL, CKPN, and LAR have a significant positive effect on BOPO. The effect of NPL, CKPN, and LAR is significantly negative on CAR. The effect of the BOPO variable on CAR is positive but insignificant. Meanwhile, the effect of NPL, CKPN, LAR through BOPO as an intervening variable on CAR is negative and insignificant. The research results imply that, in the future, banks can control the number of non-performing loans so that the cost of funds reserved for problem loans does not increase.